Optimization of an E. coli L-rhamnose-inducible expression vector: test of various genetic module combinations - Wegerer, Angelika; Sun, Tianqi; Altenbuchner, Josef (BMC biotechnology, 2008)
A capable expression vector is mainly characterized by its production efficiency, stability and induction response. These features can be influenced by a variation of modifications and versatile genetic modules. We examined miscellaneous variations of a rhaPBAD expression vector. The introduction of a stem loop into the translation initiation region of the rhaPBAD promoter resulted in the most significant improvement of eGFP expression. Starting from this plasmid, we constructed a set of expression vectors bearing different genetic modules like rop, ccdAB, cer and combinations thereof, and tested the efficiency of expression and plasmid stability. The plasmid pWA21, containing the stem loop, one cer site and rop, attained high expression levels accompanied by a good stability, and on that score seems to be a well-balanced choice. We report the generation of variations of the rhaPBAD expression vector and characterization hereof. The genetic modules showed a complex interplay, therefore two positive effects combined sometimes resulted in a disadvantage.